2013
DOI: 10.1002/jmv.23787
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of HCV‐4d in Turkey: the curious case of Kayseri Province

Abstract: In Turkey, genotype 1, especially type 1b virus, causes approximately 90% of these infections, while types 2, 3, and 4 exist, albeit in low prevalences and are due to relatively recent and limited introductions. Two recent reports from Kayseri, a relatively large city in Central Anatolia, indicated unusually high prevalence for type 4 infections in the province reaching a 35% among patients admitted to hospitals for treatment of chronic hepatitis C. In this study, the origin, the demographic history, and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…This high proportion was significantly higher than the average prevalence of 1.4% reported for type 4 HCV infections in Turkey (15). It was shown recently that Kayseri genotype 4 isolates were closely related to subtype 4d sequences (13,16).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…This high proportion was significantly higher than the average prevalence of 1.4% reported for type 4 HCV infections in Turkey (15). It was shown recently that Kayseri genotype 4 isolates were closely related to subtype 4d sequences (13,16).…”
Section: Introductionmentioning
confidence: 58%
“…In Turkey, among HCV infections, genotype 1b was reported to be the most common one (90%), while types 2, 3, and 4 exist, with lower prevalence. However, recently, there has been an increase in HCV genotype 4 infections in Turkey (9)(10)(11)(12)(13). Two studies from Kayseri reported an unusually high proportion of genotype 4 infections reaching up to 35% among the patients, who were admitted to the hospitals for treatment of CHC (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…We note, however, that our subtype 4d dataset only offers limited insights and additional sampling efforts, in particular in the Horn of Africa (Sudan, Ethiopia, Eritrea and Somalia), are needed to shed light on the spatial dispersal patterns. Additional sampling is also required to evaluate the role of Saudi Arabia in the global HCV4d spatial circulation, and may prove useful in establishing the presence and nature of links with the 4d epidemics in Turkey58 and with the European 4d epidemic among injecting drug users and HIV-1 co-infected MSM2959.…”
Section: Discussionmentioning
confidence: 99%
“…HCV‐genotypes 1 and 3 are worldwide distributed . Genotypes 1 and 2 are endemic in Western African countries (Burkina Faso, Ghana, Guinea Bissau, Republic of Benin, and Nigeria) but sporadically found also in Italy, genotypes 1 and 4 predominates in the Democratic Republic of Congo and Gabon and genotype 4 in Central and Middle East Africa so as in Turkey . HCV genotype 3 is endemic in Asia (39% of all infections), where also genotype 6 is widely distributed in the Southeast regions .…”
Section: Phylogenesis and Phylodynamic Of Hepatitis C Virusmentioning
confidence: 99%
“…[111][112][113] Both HCV genotypes and subtypes 114 are differently distributed around the world. 115 120,[125][126][127][128][129][130][131] HCV genotype 3 is endemic in Asia (39% of all infections), where also genotype 6 is widely distributed in the Southeast regions. 132 Genotype 5 is the most common HCV genotype in South Africa and in Belgium and genotype 7 has been detected only in Central African immigrants tested in Canada.…”
Section: The Phylogeny Of Genotypes B and Cmentioning
confidence: 99%